Nutritional status and physical development of high-performance combat athletes in Lithuania - Baranauskas, M.; Tubelis, L.; Stukas, R.; Svedas, E.; Samsoniene, L.; Karanauskiene, D. (Education. Physical training. Sport, 2014)
Background. Adequate nutrition is inseparable from athletes` optimal physical development and achieved sports performance. Preparing for the Olympic Games athletes` nutrition must meet certain requirements. Only under appropriate nutrition conditions athletes are enabled to maximize their adaptation to physical loads. Hypothesis: nutrition of Lithuanian high performance athletes in combat sports is adequate. Research aim was to assess nutrition profile and physical development of Lithuanian high performance athletes in combat sports. Methods. During the competition preparation period of 2012, the actual diets of Lithuanian elite boxers (n = 14), and the Greco-Roman wrestlers (n = 29) were tested and evaluated. Body composition parameters and physical development of combat athletes were assessed using BIA tetra - polar electrode method. Athletes` actual diets were established using the actual dietary survey method. Results. Muscle and fat mass indexes of boxers and Greco-Roman wrestlers, 7.5 ± 3.8 and 5.4 ± 2.0 respectively, show that effective complex preparation measures ensure optimal body condition status of athletes. Nevertheless, the diets of combat sport athletes do not meet the requirements: irrational use of proteins, not enough carbohydrates and polyunsaturated fatty acids, including omega-6 and omega-3 fatty acids, vitamins D, B1, PP, minerals, manganese, zinc, calcium and copper, too much intake of fat, saturated fatty acids and cholesterol. Conclusion. The existing diets of Lithuanian elite combat sports athletes cannot ensure their maximal adaptation to physical loads and must be optimized, individualized and adjusted, adding dietary supplements with extra carbohydrates, essential fatty acids, vitamins, minerals, and in exceptional cases, nutritional supplements with essential amino acids.